Update on biphasic anaphylaxis. Issue 4 (August 2016) - Lee, Sangil; Sadosty, Annie T.; Campbell, Ronna L.
Abstract : Purpose of review: Biphasic anaphylaxis is a well documented complication of anaphylaxis, but it has been inconsistently defined in the literature. Analysis of contemporary studies of biphasic anaphylaxis based on modern definitions is needed. Recent findings: The rate of biphasic reactions in contemporary literature ranges from 0.4 to 14.7% depending on the study population. Observational studies have reported risk factors associated with the development of biphasic reactions; however, findings have been inconsistent and of questionable generalizability. Although life-threatening biphasic reactions are rare, up to 50% of biphasic reactions will require treatment with epinephrine. Early epinephrine administration may have a role in prevention of biphasic reactions, but the role of steroids needs further investigation. The optimal duration of observation is yet to be determined. Summary: Given the relative rarity of life-threatening biphasic anaphylaxis and the new context of the NIAID/FAAN standardized definition, further research regarding biphasic anaphylaxis is needed to better elucidate the care model for anaphylaxis patients with a focus on: prevention of biphasic reactions; identification of patients at increased risk of a biphasic reaction; determination of appropriate observation strategies for anaphylaxis patients; and patient education and preparation for management of potential biphasic reactions.